Importance of oral health in mental health disorders: An updated review - Hans Erling Skallevold; Nabin Rokaya; Natthamet Wongsirichat; Dinesh Rokaya (Elsevier, 2023)
Background: Mental disorders are indeed an expanding threat, which requires raised awareness, education, prevention, and treatment initiatives nationally and globally. This review presents an updated review on the relationships between oral health and mental health disorders and the importance of oral health in mental health disorders. Method: A literature search was done regarding mental disorders and oral health approaches in Google Scholar and PubMed from the year 1995 until 2023. All the English-language papers were evaluated based on the inclusion criteria. Publications included original research papers, review articles and book chapters. Results: Common mental disorders include depression, anxiety, bipolar disorder, Schizophrenia, dementia, and alcohol and drug use disorders. The interplay of oral health and mental disorders involves dysregulated microbiome, translocated bacteria, and systemic inflammation, among others. Conclusion: There is a complex relationship between mental disorders and oral diseases. Various oral health problems are associated with mental health problems. The interplay of oral health and mental disorders involves dysregulated microbiome, translocated bacteria, and systemic inflammation, among others. Mental health nurses including physicians and dental professionals should be involved in the oral health care of mental health disorder patients. Therefore, multidisciplinary should be involved in the care of mental health disorders, and they should consider oral health care as an essential part of their care for patients with mental health disorders. Future investigations should strive to elucidate the exact biological relationships, to develop new directions for treatment.